1968
DOI: 10.1037/h0025749
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of posthypnotic behavior outside the experimental setting.

Abstract: 17 excellent hypnotic Ss were asked to participate in a 2-day experiment which would involve many personality tests. On the 1st day Ss were given the suggestion that for the next 48 hr. they were to respond by touching their forehead each time they heard the word "experiment." The E tested the suggestion in the experimental setting, but unbeknownst to the Ss the critical test came in the waiting room: the secretary-receptionist tested Ss as they were leaving the building on the 1st day and again as they arrive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

1968
1968
2001
2001

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 13 publications
5
46
1
Order By: Relevance
“…It has been well documented that simulators respond to their perception of the nature of experimental conditions and the behavior that those conditions imply. For example, in a study of posthypnotic behavior (Orne, Sheehan, & Evans, 1968), simulators responded significantly more often than hypnotic Ss to an informal test of a posthypnotic suggestion. Little evidence, however, bears on the assertion that simulators are sensitive to contextual features such as the order of testing.…”
Section: Role Of Contextmentioning
confidence: 99%
“…It has been well documented that simulators respond to their perception of the nature of experimental conditions and the behavior that those conditions imply. For example, in a study of posthypnotic behavior (Orne, Sheehan, & Evans, 1968), simulators responded significantly more often than hypnotic Ss to an informal test of a posthypnotic suggestion. Little evidence, however, bears on the assertion that simulators are sensitive to contextual features such as the order of testing.…”
Section: Role Of Contextmentioning
confidence: 99%
“…Those similarities include observer blinds, control groups that differ from the experimental only on some form of demand The data of this project seem to agree in general with the results of Orne's (1959Orne's ( , 1968and Orne & Evans, 1965) (Nixon, 1965) utilizing an appropriate control group fails to provide evidence for the efficacy of conditioning or modeling and conditioning techniques to improve study behavior.…”
Section: Demand Characteristics and Modification Of Behaviorsupporting
confidence: 67%
“…Orne (1959Orne ( , 1968 and Orne and Evans (1965) (1966,1968). That study, reviewed above, suggests that such variables might be well utilized in applied settings to modify behavior.…”
Section: Demand Characteristics Literature Reviewmentioning
confidence: 99%
“…I n more recent experiments, Orne and his associates (Orne & Evans, 1966 Sheehan, & Evans, 1968;Sheehan, 1969) have been concerned with further differences between the performance of hypnotic and simulating subjects. These experiments have carefully specified dependent measures and experimental contingencies.…”
Section: Methodological Critiquementioning
confidence: 99%
“…The most important experimental work carried out by Orne and his associates (Evans & Thorn, 1966;Orne, 1959;Orne & Evans, 1966;Orne, Sheehan & Evans, 1968;Sheehan, 1969) has attempted to delineate the essential characteristics of the trance state. These investigators contend that behavioral changes observed subsequent to hypnotic induction procedures are a function not only of the trance state, but also of the "demand characteristics" associated with the hypnotic situation.…”
Section: Overviewmentioning
confidence: 99%